A Phenomenological Study of Health Requirements regarding School Activity in Post-Corona Period - Hamid Chekaveh; Mohsen Shakeri; Hossain Hassani (Journal of Social Behavior and Community Health)
Background: In Iran, from the academic year 2021-2022, it was decided to reopen all schools. It is of great importance that the activities of schools be accompanied by principles, solutions, and requirements; so, concerns about students and school staff contracting this disease will be reduced. The present investigates the experiences of elementary school principals in Roodan city, in Hormozgan Province, Iran, about health requirements of school activity during post-corona era. Methods: This was a qualitative and phenomenological study. Data were analyzed by Smith's method after theoretical saturation of data obtained from an in-depth semi-structured interview. The interview contained 12 principals of elementary schools in Roodan city in the academic year of 2021-2022, who were selected through purposive sampling. Results: The experiences of elementary school principals about school activities were obtained in the form of 3 main themes including executive measures (provision of disinfectants, improvement of school infrastructure, absence of sick students and teachers in school, safe distance, creating a happy and safe environment for students to attend, and seeking support from benefactors and parents counseling sessions), educational and promotion-interventional measures (holding classes and remedial measures, teaching health issues to students, informing parents, environmental and virtual information, and counseling sessions), and supervisory measures (supervision of students, teachers, principals, and assistants of the school). Conclusions: The results of examining the experiences of elementary school principals about reopening of schools in the post-corona period showed that there is a need for many facilities and measures. Moreover, capable principals face various challenges and need to work with organizations, officials, students, and families.